2023
DOI: 10.3389/fenvs.2023.1104679
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable trend in COVID-19 research: An environmental perspective

Abstract: Coronavirus disease 2019 (COVID-19) has spread across the globe producing hundreds of thousands of deaths, shutting down economies, closing borders and causing havoc on an unprecedented scale. Its potent effects have earned the attention of researchers in different fields worldwide. Among them, authors from different countries have published numerous research articles based on the environmental concepts of COVID-19. The environment is considered an essential receptor in the COVID-19 pandemic, and it is academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 184 publications
0
1
0
Order By: Relevance
“…In fact, using contaminated water in any WASH practice, above all hand washings, defeats the very objective of sanitation and disease prevention [36,42]. Furthermore, several studies have reported the presence of SARS-CoV-2 virus in wastewater, where it can remain viable for a few days, subject to the environmental conditions [43][44][45][46][47][48].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In fact, using contaminated water in any WASH practice, above all hand washings, defeats the very objective of sanitation and disease prevention [36,42]. Furthermore, several studies have reported the presence of SARS-CoV-2 virus in wastewater, where it can remain viable for a few days, subject to the environmental conditions [43][44][45][46][47][48].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Multiple studies have been conducted on the cause and spread of COVID-19. Notably, from an environmental perspective, some studies have suggested that meteorological factors, including temperature, humidity, and precipitation, affect the transmission of COVID-19; others report that the rate of COVID-19 transmission varies depending on air quality, various pollutants, and water and soil characteristics (Han et al, 2023;Cheval et al, 2020;SanJuan-Reyes et al, 2021;Annlet et al, 2021;Vadiati et al, 2023;Rume and Islam, 2020;El Zowalaty et al, 2020). As the relationship between infectious diseases, including COVID-19, and environmental sectors is being studied, and more environmental research is needed for a sustainable society, it is time for central and local governments to pursue environmental measures and policies from a long-term perspective to improve the environment.…”
mentioning
confidence: 99%